Inside information in bank lending and the European insider directive - Günter Franke (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1989)
The European Community has passed the European Insider Directive which prohibits insider trade in common stock and debt securities. Hence banks are not allowed to sell debt securities when they recieve unfavorable inside information on their borrowers. Until now, German banks have not only been allowed, but even have been expected to collect inside information and to react fast on unfavorable information to protect their solvency and hence the stability of the financial system. This paper analyses the effects of the EC - Directive on bank lending and finds that the substitutes for selling debt securities appear to generate a higher social cost than the sale of debt securities. Therefore banks should be granted the privilege to sell debt securities on unfavorable inside information.
Keywords: 330